Iron in silicate glasses and melts: Implications for volcanological processes - Losq, Charles Le; Cicconi, Maria Rita; Neuville, Daniel R. (Wiley Blackwell, 2021)
Iron is present in magmas at concentrations ranging from less than 1 wt% to more than 10 wt% in two valence states. In general, Fe 2+ is a network modifier in the melt structure while Fe 3+ is a weak network former. The ratio Fe 3+ /(Fe 3+ +Fe 2+ ) depends on temperature, pressure, oxygen fugacity, and melt composition. Parametric models allow its calculation, but the complex links between melt composition, iron oxidation state, and coordination can be further rationalized using a ionic-polymeric model. Constraining concentration and oxidation state of iron is critical for determining magma density and viscosity, which drive exchanges of matter and heat in the Earth. At high pressures, changes in the coordination of elements, including iron, yield a stiffening and densification of magmas, potentially influencing dynamic and geochemical processes. Near surface, crystallization of Fe-bearing phases changes the residual melt composition, including iron content and oxidation state as well as volatile concentration, ultimately driving large changes in density and viscosity of magmas, and, hence, in the dynamic of fluid flow in volcanic systems. The complex interplay between magma iron content and oxidation state, major element chemistry, crystal and volatile contents thus can play a large role on the dynamic of volcanic systems.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Influences on crystallization and degassing in magmatic systems; Iron distribution in the different terrestrial envelopes; Physical properties: highlights on density and viscosity; Redox equilibrium in melts